A high corrosion resistance, flame retardancy and high thermal conductivity die-casting magnesium alloy and preparation method thereof
By optimally combining Zn, La, HRE, Zr, Ca and other elements, a highly corrosion-resistant, flame-retardant and high thermal conductivity die-cast magnesium alloy with a specific microstructure is prepared, which solves the problem of changes in thermal conductivity, corrosion resistance and flame retardancy of magnesium alloys when improving mechanical properties. Poor problem, high performance and low cost magnesium alloy materials are achieved.
Patent Information
- Application Number
- CN202411385115.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-30
AI Technical Summary
While improving the mechanical properties of existing magnesium alloys, the thermal conductivity, corrosion resistance and flame retardant properties of existing magnesium alloys usually deteriorate, and the flame-retardant magnesium alloys cause adhesive mold and thermal crack defects by adding Ca, making molding difficult and waste rate high.
Through preferential combinations ZN, LA, HRE, ZR, CA and other elements, prepare high-corrosion-resistant high-conducting high-conducting hydraulic-casting magnesium alloy with α-MG substrate phase, LA2MG17 phase, long cycle structure X phase-mg12hrezn, and ZR particles.
It achieves high thermal conductivity (128~143 W·(m·K)-1), high ignition point (above 880℃), excellent corrosion resistance (corrosion rate 0.047~0.083mg/cm2/day) and high mechanical properties. performance (yield strength ≥ 160.2MPa), while reducing manufacturing costs.
Smart Images

Figure CN118880140B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnesium alloy materials, and in particular to a high corrosion-resistant, flame-retardant and high thermal conductivity die-cast magnesium alloy and a preparation method thereof. Background Art
[0002] The density of magnesium is 1.74 g / cm 3 , about 2 / 3 of aluminum and 1 / 4 of iron. It has a series of characteristics such as recyclability, light specific gravity, high specific strength and specific stiffness, good damping and thermal conductivity, and good shock absorption. It is widely used in communications, electronics, automobiles, chemicals, aerospace and other fields. It is known as the "21st century green engineering material". my country is the country with the richest magnesium resources in the world, and its available magnesium reserves account for 70% of the world's total reserves. At present, my country's dependence on iron ore and lithium ore has reached 82% and 65% respectively. The large-scale application of magnesium alloys has very important strategic significance for energy conservation and emission reduction, and alleviating the shortage of metal mineral resources in my country.
[0003] Most magnesium alloy parts are die-cast. Die-cast magnesium alloys have the advantages of low melting energy consumption, fast filling speed, fast solidification speed, short die-casting cycle, and long mold service life. They are very suitable for preparing thin-walled and near-net-shape complex parts, especially for many 3C, communication, and electronic products. They meet the requirements of highly integrated, lightweight, anti-collision, flame retardant, heat dissipation, and corrosion resistance. The thermal conductivity of pure magnesium is 158W / m·k, second only to pure copper and pure aluminum metal materials, but the low strength of pure magnesium affects its performance as a structural part. The mechanical properties of magnesium alloys obtained by the most commonly used alloying method are significantly improved, but their thermal conductivity is significantly reduced. For example, the commonly used cast magnesium alloy AZ91D has a yield strength of 150MPa in the cast state (cast magnesium is about 21MPa), but the thermal conductivity is only 51.2W / (m·K) (only about 1 / 3 of pure magnesium). Therefore, it is urgent to develop a die-cast magnesium alloy with both high thermal conductivity and medium mechanical strength. Since the melting point of magnesium alloy is about 650℃ and its chemical properties are too active, when used as parts of electronic battery housings, cars, trains and other transportation vehicles, it is easy to ignite and release a lot of heat in a fire, which is one of the reasons that limit the application of magnesium alloy in the transportation field. Therefore, the development of flame-retardant magnesium alloy has become a hot spot for the research and development and application of magnesium alloy. Existing flame-retardant magnesium alloys mainly increase the ignition point of magnesium alloys by adding alkaline earth element Ca, but due to the addition of too much Ca, magnesium alloys are prone to mold sticking and hot cracking defects, which makes die casting difficult, resulting in a high scrap rate. The standard electrode potential of magnesium is -2.37V, which is the lowest among all metal structural materials, and the common second phase potential in magnesium alloys is generally much higher than that of magnesium matrix, which is prone to galvanic corrosion and leads to poor corrosion resistance of magnesium alloys. In addition, when magnesium alloys are placed in air or solution, a thin oxide film mainly composed of MgO is easily generated on the surface, and its PBR (Pilling-Bedworth Ratio, the volume ratio of oxide to metal consumed to form the oxide) is less than 1, which cannot effectively cover the surface of the magnesium matrix, and thus does not have good protection. At the same time, the corrosion product film of magnesium is mainly composed of Mg(OH)2, which has a lamellar, loose and porous structural characteristic and cannot effectively prevent the expansion of corrosion. For aluminum or titanium metals, although their standard electrode potential is also very low, a dense oxide film (PBR>1) is formed on the surface of aluminum and titanium, which can effectively prevent the continuous expansion of the corrosive medium. Therefore, aluminum and titanium have good corrosion resistance. The Chinese patent document with publication number CN103469040A discloses a flame-retardant magnesium alloy with composite addition of rare earth Nd and Y and its ignition point test method. The developed Mg-Al-Zn-RE alloy contains a high content of easily soluble elements Al and Zn, and has low thermal conductivity. Rare earth is added but the ignition point is only 598°C, and the practical application value is not high.A Chinese patent document with publication number CN111304510A discloses a high-strength and high-corrosion-resistant ternary magnesium alloy and a preparation method thereof. The ternary magnesium alloy includes the following weight percentage element components Y: 8-12%, Al: 0.6-3%, and the balance is Mg. After the ternary magnesium alloy is immersed in a 3.5wt% NaCl solution for 336 hours, the corrosion rate can be less than 0.2mg / cm. 2 / day, while the corrosion resistance needs to be further improved, the addition of 8-12% rare earth Y element increases the cost, which is not conducive to actual industrial promotion and application.
[0004] There is usually an inverse relationship between the thermal conductivity and strength, corrosion resistance, flame retardancy and other functional properties of magnesium alloys. When the strength of magnesium alloys is improved, their thermal conductivity, corrosion resistance, flame retardancy and other properties usually deteriorate. By adding low-cost alloying elements, the development of structural and functional integrated magnesium alloys with high thermal conductivity, high strength, high ignition point and excellent corrosion resistance is of great significance to the development and application of magnesium alloys. Summary of the invention
[0005] The purpose of the present invention is to provide a high corrosion-resistant, flame-retardant and high thermal conductivity die-cast magnesium alloy, which has high thermal conductivity, flame retardancy, high corrosion resistance and relatively high mechanical properties.
[0006] To achieve the above object, the technical solution of the present invention is:
[0007] A high corrosion-resistant, flame-retardant and high thermal-conductivity die-cast magnesium alloy, wherein the weight percentages of the components in the die-cast magnesium alloy are Zn: 0.3-1.2%, La: 2.0-3.5%, HRE: 0.2-0.6%, Zr: 0.3-0.6%, Ca: 0.1-0.3%, Fe≤0.005%, Cu≤0.01%, Ni≤0.001%, HRE is any one of the heavy rare earth elements Y and Gd, and the balance is Mg.
[0008] Furthermore, the die-cast magnesium alloy phase includes a spherical α-Mg grain matrix phase, a network-like La2Mg 17 phase, long period structure X phase-Mg 12 HREZn and Zr particle precipitation phase; the network-like La2Mg 17 phase is distributed along the α-Mg grain boundary, and the long-period structure X phase-Mg 12 HREZn precipitates and pins on La2Mg 17 phase; the Zr particles provide heterogeneous nucleation cores for α-Mg grains; the spherical α-Mg grain size is 3 to 15 μm, and the Zr particle size is 100 to 200 nm; the thermal conductivity of the die-cast magnesium alloy is 128 to 143 W·(m·K) -1The ignition point is above 880℃, and the corrosion rate in 3.5wt% NaCl solution is 0.047~0.083mg / cm 2 / day, yield strength ≥160.2MPa.
[0009] Another object of the present invention is to provide a method for preparing the above-mentioned high corrosion-resistant, flame-retardant and high thermal conductivity die-cast magnesium alloy, comprising the following steps:
[0010] 1) Put the recycled magnesium ingot, zinc block and calcium block into the crucible of the resistance furnace, heat it to 690-720°C, sprinkle commercial RJ-5 flux into the crucible, wait for the charge to be completely melted and evenly stirred, and then heat the magnesium melt to 730-750°C, slowly add the rare earth metal La and HRE into the magnesium melt and stir for 10-15 minutes, sprinkle RJ-5 flux into the melt and stir evenly, then heat the magnesium melt to 750-780°C, add Mg-Zr master alloy and pass argon into the melt for 5-10 minutes to accelerate alloying and melt homogenization;
[0011] 2) introducing H2 / Ar mixed gas into the bottom of the crucible and sprinkling refining agent into the melt for refining, after refining, slag is removed and RJ-5 flux is sprinkled into the melt for covering; the volume fraction of H2 in the H2 / Ar mixed gas is 5-8%;
[0012] 3) The magnesium melt refined in step 2) is heated to 750-770° C., kept at this temperature for 10-20 minutes, and then the resistance furnace is powered off. The temperature is naturally cooled to 700-730° C., and then samples are taken for testing to control the impurity content of Fe≤0.005%, Cu≤0.01%, and Ni≤0.001%. After the alloy composition is qualified, a magnesium alloy ingot is cast.
[0013] Furthermore, in step 1), the flow rate of the argon gas introduced is 15-20 L / min, in step 2), the flow rate of the 5-8% H2 / Ar mixed gas introduced is 15-20 L / min, and the refining time is 15-25 min.
[0014] Furthermore, the refining agent in step 2) is a mixture of commercial RJ-6 flux and MgF2, the amount of the refining agent added is 2% of the weight of the magnesium melt, and the weight percentage of MgF2 in the refining agent is 10-30%. The total amount of RJ-5 flux in step 1) and step 2) is 2% of the weight of the magnesium melt.
[0015] Furthermore, in the step 3), the casting of the magnesium alloy ingot is performed under the protection of a mixed gas of SF6 and CO2, and the volume ratio of SF6 is 0.1 to 0.3%.
[0016] The present invention has the following beneficial effects:
[0017] The high corrosion resistant, flame retardant and high thermal conductivity die-cast magnesium alloy disclosed in the present invention is prepared for the first time by optimizing and combining the types and contents of elements to obtain a high corrosion resistant, flame retardant and high thermal conductivity die-cast magnesium alloy having an α-Mg matrix phase, a La2Mg 17 phase, long period structure X phase-Mg 12 Die-cast magnesium alloys with HREZn and Zr particle phase composition characteristics: (1) The alloying elements Zn and HRE with large solid solubility are small in content and mainly in the form of X-phase-Mg 12 HREZn exists in the grain boundary area, avoiding solid solution in magnesium and causing a decrease in thermal conductivity; La2Mg formed by adding rare earth La 17 The phase is distributed in the grain boundary in a network shape, which inhibits the formation of microporosity and improves the die-casting process performance of the alloy; the long-period structure X phase-Mg 12 Precipitation and pinning of HREZn strong plastic phase in La2Mg 17 phase and inhibits grain growth, while adding a small amount of Zr brings about a fine grain effect and a long period structure X-phase-Mg 12 The second phase strengthening effect caused by HREZn makes the alloy have higher strength without reducing the thermal conductivity. (2) Compared with the traditional single addition of flame retardant element Ca, the present invention adds Ca, La and HRE elements with excellent flame retardant properties. When the magnesium alloy is exposed to the atmosphere at high temperature, a layer of CaO / La2O3 / HRE2O3 composite oxide film (Pilling-Bedworth Ratio>1) with excellent protective properties will be generated on the surface of the alloy. The film has a dense structure, strong spreadability, is solid at high temperature and is not easy to volatilize, which hinders the further oxidation of the magnesium alloy matrix. The ignition point of the magnesium alloy is significantly increased to above 880℃, while the ignition point of common magnesium alloys such as AZ31, AZ80, AZ91, ZK60, etc. is only 550-600℃. In addition, the total content of Ca and HRE elements in the present invention is less than 0.9%, of which the content of HRE elements does not exceed 0.6%, which ensures low cost while avoiding the formation of Mg6Ca2Zn3 brittle phase, achieving a good match between strength and flame retardant properties. (3) By the attached Figures 2~4 It can be seen that the fine-grained alloy prepared by the present invention has a large amount of La2Mg distributed at the grain boundaries. 17 Phase and long period structure X phase-Mg 12 The HREZn precipitated phase wraps and isolates the primary α-Mg grains, making it difficult for the chain corrosion reaction of the α-Mg, which is easily corroded as the anode, to spread. The "net-like" precipitated phase cuts off the continuity of the corrosion reaction, and the corrosion product film contains a large amount of La2O3 / HRE2O3 composite oxide film with Pilling-Bedworth Ratio>1, which makes the corrosion product film have high compactness, thus showing high corrosion resistance. The corrosion rate of AZ31 magnesium alloy is about 4.5mg / cm 2 / day, the corrosion rate of AZ91 magnesium alloy is about 1.58mg / cm2 / day, while the corrosion rate of the magnesium alloy of the present invention is only 0.047-0.083 mg / cm 2 / day, showing extremely high corrosion resistance.
[0018] In the preparation method of the present invention, H2 / Ar mixed gas containing 5-8% H2 is introduced for degassing and refining, hydrogen is used as a deoxidizer to remove oxygen in the melt, and the gas and inclusions existing in the melt are removed in the process of the H2 / Ar mixed gas flow stirring the melt and the bubbles floating up, thereby improving the purity and corrosion resistance of the alloy. Subsequently, a sedimentation treatment process of high-temperature standing and power-off cooling is performed to precipitate impurity elements such as Fe, Si, Ni dissolved in magnesium and sink to the bottom and be removed, thereby further improving the corrosion resistance of the magnesium alloy. In addition, the H2 / Ar mixed gas mixed with a small amount of H2 is safe to use and operate, and will not bring the risk of hydrogen explosion.
[0019] The active materials of the present invention are all relatively cheap conventional elements with sufficient mineral resources reserves. The maximum content of alloying elements is only 5.2%. The raw material cost is low, and recycled waste magnesium with complex composition and more impurities can be used as raw material to manufacture high corrosion-resistant, flame-retardant and high thermal conductivity die-casting magnesium alloys, thereby reducing manufacturing costs and improving production efficiency. It can reduce costs and increase efficiency for enterprises, and promote the benign and healthy development of magnesium alloy material technology and heat treatment-free integrated die-casting industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The XRD pattern of the die-cast magnesium alloy prepared in Example 1;
[0021] Figure 2 This is a scanning electron microscope backscattered electron image of the die-cast magnesium alloy obtained in Example 2, magnified 500 times;
[0022] Figure 3 This is a scanning electron microscope backscattered electron image of the die-cast magnesium alloy obtained in Example 1, magnified 5000 times;
[0023] Figure 4 The secondary electron image of the die-cast magnesium alloy obtained in Example 1 is magnified 5000 times by a scanning electron microscope. (The sample was observed on a JEOL JXA-8100 scanning electron microscope (SEM) equipped with an OXFORD 7412 energy dispersive spectrometer (EDS), and the inclusion fraction of the alloy was estimated using Image J software; the phase composition was analyzed on a D / MAX-RC X-ray diffractometer (XRD) using a Cu target; the plate-shaped tensile sample was subjected to a room temperature (293K) tensile test on a DNS200 universal material testing machine, with a tensile speed of 2 mm•min -1Thermal conductivity was measured on a NETZSCH LFA427 laser thermal conductivity meter at room temperature (293K). Corrosion resistance was measured by immersing the sample in a 3.5wt% NaCl solution for 7 days at room temperature (293K) to measure the corrosion rate. Ignition point of the alloy was tested by heating a block sample with a size of 10mm×10mm×10mm from room temperature at a heating rate of 5°C / min until the sample was completely burned). DETAILED DESCRIPTION
[0024] For a better understanding of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. However, the protection scope of the present invention is not limited to the description scope of the embodiments. Example 1
[0025] A method for preparing a highly corrosion-resistant, flame-retardant and highly thermally conductive die-cast magnesium alloy comprises the following steps:
[0026] 1) Put the regenerated magnesium ingot, zinc block and calcium block into the crucible of the resistance furnace, heat it to 710°C, sprinkle commercial RJ-5 flux into the crucible, wait for the charge to be completely melted and evenly stirred, and then heat the magnesium melt to 740°C, slowly add the rare earth metals La and Y into the magnesium melt and stir for 13 minutes, sprinkle RJ-5 flux into the melt and stir evenly, then heat the magnesium melt to 760°C, add Mg-Zr master alloy and continuously introduce argon gas at a flow rate of 18L / min into the melt for 8 minutes to accelerate alloying and melt homogenization;
[0027] 2) introducing H2 / Ar mixed gas containing 7% H2 into the bottom of the crucible and sprinkling refining agent into the melt for refining, after refining, slag is removed and RJ-5 flux is sprinkled into the melt for covering; the flow rate of the introduced 7% H2 / Ar mixed gas is 18 L / min, and the refining time is 20 min; the refining agent is a mixture of commercial RJ-6 flux and MgF2, and the weight percentage of MgF2 is 20%; the amount of the refining agent added is 2% of the weight of the magnesium melt, and the total amount of RJ-5 flux used in step 1) and step 2) is 2% of the weight of the magnesium melt;
[0028] 3) The magnesium melt refined in step 2) is heated to 760°C, kept at this temperature for 15 minutes, and then the resistance furnace is powered off. The temperature is naturally cooled to 710°C, and then samples are taken for testing. After the alloy composition is tested to be qualified, a magnesium alloy ingot is cast. The cast magnesium alloy ingot is cast under the protection of a mixed gas of SF6 and CO2, and the volume ratio of SF6 is 0.2%.
[0029] The high corrosion resistance, flame retardancy and high thermal conductivity die-cast magnesium alloy of this embodiment is tested. The weight percentage of each component is Zn: 0.7%, La: 2.8%, Y: 0.4%, Zr: 0.4%, Ca: 0.2%, Fe: 0.004%, Cu: 0.008%, Ni: 0.0008%, and the balance is Mg. The die-cast magnesium alloy phase includes a spherical α-Mg matrix phase, a network-like La2Mg 17 phase, long period structure X phase-Mg 12 YZn and Zr particle precipitation phase, spherical α-Mg matrix phase grain size of 3 ~ 15μm, network La2Mg 17 phase is distributed along the α-Mg grain boundary, and the long-period structure X phase-Mg 12 YZn strong plastic phase precipitation and pinning grain boundary network and inhibit grain growth, 100 ~ 200nm size Zr-rich particles provide heterogeneous nucleation core for Mg grains, such as Figure 1 The XRD patterns and Figure 3 5000 times scanning electron microscope backscattered electron image, Figure 4 As shown in the 5000x scanning electron microscope secondary electron image, a large amount of La2Mg is distributed at the grain boundaries of the magnesium alloy. 17 Phase and long period structure X phase-Mg 12 The YZn precipitated phase wraps and isolates the primary α-Mg grains, making it difficult for the chain corrosion reaction of α-Mg, which is easily corroded as the anode, to spread. The "net-like" precipitated phase cuts off the continuity of the corrosion reaction. The die-cast magnesium alloy has 135W·(m·K) -1 Thermal conductivity, ignition point of 900℃ and corrosion rate of 0.064mg / cm in 3.5wt% NaCl solution 2 / day's corrosion resistance, fine grain strengthening and second phase strengthening effects make the magnesium alloy have a yield strength of 162.3MPa. Example 2
[0030] A method for preparing a highly corrosion-resistant, flame-retardant and highly thermally conductive die-cast magnesium alloy comprises the following steps:
[0031] 1) Put the regenerated magnesium ingot, zinc block and calcium block into the crucible of the resistance furnace, heat it to 690°C, sprinkle commercial RJ-5 flux into the crucible, wait for the charge to be completely melted and evenly stirred, and then heat the magnesium melt to 730°C, slowly add the rare earth metals La and Y into the magnesium melt and stir for 10 minutes, sprinkle RJ-5 flux into the melt and stir evenly, then heat the magnesium melt to 750°C, add Mg-Zr master alloy and continuously introduce argon gas at a flow rate of 15L / min into the melt for 5 minutes to accelerate alloying and melt homogenization;
[0032] 2) introducing H2 / Ar mixed gas containing 5% H2 into the bottom of the crucible and sprinkling refining agent into the melt for refining, after refining, slag is removed and RJ-5 flux is sprinkled into the melt for covering; the flow rate of the introduced 5% H2 / Ar mixed gas is 15 L / min, and the refining time is 15 min; the refining agent is a mixture of commercial RJ-6 flux and MgF2, and the weight percentage of MgF2 is 10%; the amount of the refining agent added is 2% of the weight of the magnesium melt, and the total amount of RJ-5 flux used in step 1) and step 2) is 2% of the weight of the magnesium melt;
[0033] 3) The magnesium melt refined in step 2) is heated to 750°C, kept at this temperature for 10 minutes, and then the resistance furnace is powered off. The temperature is naturally cooled to 700°C, and then samples are taken for testing. After the alloy composition is tested to be qualified, a magnesium alloy ingot is cast. The cast magnesium alloy ingot is cast under the protection of a mixed gas of SF6 and CO2, and the volume ratio of SF6 is 0.1%.
[0034] The high corrosion resistance, flame retardancy and high thermal conductivity die-cast magnesium alloy of this embodiment is tested. The weight percentage of each component is Zn: 0.3%, La: 2.0%, Gd: 0.2%, Zr: 0.3%, Ca: 0.1%, Fe: 0.005%, Cu: 0.01%, Ni: 0.001%, and the balance is Mg. The die-cast magnesium alloy phase includes a spherical α-Mg matrix phase, a network-like La2Mg 17 phase, long period structure X phase-Mg 12 GdZn and Zr particle precipitation phase, spherical α-Mg matrix phase grain size of 3 ~ 15μm, network La2Mg 17 phase is distributed along the α-Mg grain boundary, and the long-period structure X phase-Mg 12 GdZn strong plastic phase precipitation and pinning grain boundary network and inhibit grain growth, 100 ~ 200nm size Zr-rich particles provide heterogeneous nucleation core for Mg grains, such as Figure 2 As shown in the 500x scanning electron microscope backscattered electron image, the α-Mg grains are La2Mg 17 Phase and long period structure X phase-Mg 12 GdZn precipitation phase wrapping; the die-cast magnesium alloy has 143 W·(m·K) -1 Thermal conductivity, ignition point of 890°C and corrosion rate of 0.083 mg / cm in 3.5wt% NaCl solution 2 / day's corrosion resistance, fine grain strengthening and second phase strengthening effects make the magnesium alloy have a yield strength of 160.2MPa. Example 3
[0035] A method for preparing a highly corrosion-resistant, flame-retardant and highly thermally conductive die-cast magnesium alloy comprises the following steps:
[0036] 1) Put the regenerated magnesium ingot, zinc block and calcium block into the crucible of the resistance furnace, heat it to 720°C, sprinkle commercial RJ-5 flux into the crucible, wait for the charge to be completely melted and evenly stirred, and then heat the magnesium melt to 750°C, slowly add the rare earth metals La and Y into the magnesium melt and stir for 10 minutes, sprinkle RJ-5 flux into the melt and stir evenly, then heat the magnesium melt to 780°C, add Mg-Zr master alloy and continuously introduce argon gas at a flow rate of 20L / min into the melt for 10 minutes to accelerate alloying and melt homogenization;
[0037] 2) introducing H2 / Ar mixed gas containing 8% H2 into the bottom of the crucible and sprinkling refining agent into the melt for refining, after refining, slag is removed and RJ-5 flux is sprinkled into the melt for covering; the flow rate of the introduced 8% H2 / Ar mixed gas is 20 L / min, and the refining time is 25 min; the refining agent is a mixture of commercial RJ-6 flux and MgF2, and the weight percentage of MgF2 is 30%; the amount of the refining agent added is 2% of the weight of the magnesium melt, and the total amount of RJ-5 flux used in step 1) and step 2) is 2% of the weight of the magnesium melt;
[0038] 3) The magnesium melt refined in step 2) is heated to 770°C, kept at this temperature for 20 minutes, and then the resistance furnace is powered off. The temperature is naturally cooled to 730°C, and then samples are taken for testing. After the alloy composition is tested to be qualified, a magnesium alloy ingot is cast. The cast magnesium alloy ingot is cast under the protection of a mixed gas of SF6 and CO2, and the volume ratio of SF6 is 0.3%.
[0039] The high corrosion resistance, flame retardancy and high thermal conductivity die-cast magnesium alloy of this embodiment is tested to have the following weight percentages: Zn: 1.2%, La: 3.5%, Y: 0.6%, Zr: 0.6%, Ca: 0.3%, Fe: 0.003%, Cu: 0.006%, Ni: 0.0006%, and the balance is Mg. The die-cast magnesium alloy phase includes a spherical α-Mg matrix phase, a network-like La2Mg 17 phase, long period structure X phase-Mg 12 YZn and Zr particle precipitation phase, spherical α-Mg matrix phase grain size of 3 ~ 15μm, network La2Mg 17 phase is distributed along the α-Mg grain boundary, and the long-period structure X phase-Mg 12 YZn strong plastic phase precipitation and pinning grain boundary network and inhibit grain growth, 100-200nm size Zr-rich particles provide heterogeneous nucleation core for Mg grains, the die-casting magnesium alloy has 128W·(m·K) -1 Thermal conductivity, ignition point of 920℃ and corrosion rate of 0.047mg / cm in 3.5wt% NaCl solution 2 / day's corrosion resistance, fine grain strengthening and second phase strengthening effects make the magnesium alloy have a yield strength of 165.4MPa. Comparative Example
[0040] A method for preparing a die-cast magnesium alloy comprises the following steps:
[0041] 1) Put the regenerated magnesium ingot, zinc block and calcium block into the crucible of the resistance furnace, heat it to 720°C, sprinkle commercial RJ-5 flux into the crucible, wait for the charge to be completely melted and evenly stirred, and then heat the magnesium melt to 750°C, slowly add the rare earth metals La and Y into the magnesium melt and stir for 10 minutes, sprinkle RJ-5 flux into the melt and stir evenly, then heat the magnesium melt to 780°C, add Mg-Zr master alloy and continuously introduce argon gas at a flow rate of 20L / min into the melt for 10 minutes to accelerate alloying and melt homogenization;
[0042] 2) Ar gas is introduced into the bottom of the crucible and a refining agent is sprinkled into the melt for refining. After refining, the slag is removed and RJ-5 flux is sprinkled in to cover the slag. The flow rate of the Ar gas is 20 L / min, and the refining time is 25 min. The refining agent is a mixture of commercial RJ-6 flux and MgF2, and the weight percentage of MgF2 is 30%. The amount of the refining agent added is 2% of the weight of the magnesium melt. The total amount of RJ-5 flux used in step 1) and step 2) is 2% of the weight of the magnesium melt.
[0043] 3) The magnesium melt refined in step 2) is heated to 770°C, kept at this temperature for 20 minutes, and then the resistance furnace is powered off. The temperature is naturally cooled to 730°C, and then samples are taken for testing. After the alloy composition is tested to be qualified, a magnesium alloy ingot is cast. The cast magnesium alloy ingot is cast under the protection of a mixed gas of SF6 and CO2, and the volume ratio of SF6 is 0.3%.
[0044] The weight percentage of each component of the die-cast magnesium alloy in this comparative example is Zn: 1.2%, La: 3.5%, Y: 0.6%, Zr: 0.6%, Ca: 0.3%, Fe: 0.006%, Cu: 0.015%, Ni: 0.0013%, and the balance is Mg. The die-cast magnesium alloy phase includes a spherical α-Mg matrix phase, a network-like La2Mg 17 phase, long period structure X phase-Mg 12 YZn and Zr particle precipitation phase, spherical α-Mg matrix phase grain size of 3 ~ 15μm, network La2Mg 17 phase is distributed along the α-Mg grain boundary, and the long-period structure X phase-Mg 12 YZn strong plastic phase precipitation and pinning grain boundary network and inhibit grain growth, 100-200nm Zr-rich particles provide heterogeneous nucleation core for Mg grains, the die-casting magnesium alloy has 115W·(m·K)-1 Thermal conductivity, ignition point of 850°C and corrosion rate of 0.102 mg / cm in 3.5 wt% NaCl solution 2 / day's corrosion resistance, fine grain strengthening and second phase strengthening effects make the magnesium alloy have a yield strength of 135.8MPa.
[0045] Comparing the comparative example with Example 3, it can be seen that compared with Example 3, since the gas used for refining in the comparative example does not contain H2 with deoxidizing effect, the oxide inclusions in the magnesium melt cannot be deeply removed, and the refining and impurity removal effect is poor, which is particularly reflected in the corrosion resistance. The corrosion rate of the comparative example is 0.102 mg / cm 2 / day is 2.17 times the corrosion rate of the magnesium alloy obtained by refining with a H2 / Ar mixed gas of 8% H2 in Example 3, and at the same time causes the impurity contents of Fe, Ni and Cu to be higher than those in Example 3, thereby affecting and causing a comprehensive decrease in the yield strength, thermal conductivity and flame retardancy of the magnesium alloy, as shown in the performance index comparison in Table 1 below.
[0046]
Claims
1. A highly corrosion-resistant, flame-retardant and highly thermally conductive die-cast magnesium alloy, characterized in that: The weight percentage of each component in the die-cast magnesium alloy is Zn: 0.3-1.2%, La: 2.0-3.5%, HRE: 0.2-0.6%, Zr: 0.3-0.6%, Ca: 0.1-0.3%, Fe≤0.005%, Cu≤0.01%, Ni≤0.001%, and the balance is Mg; the HRE is any one of the heavy rare earth elements Y and Gd; The die-cast magnesium alloy phase includes a spherical α-Mg grain matrix phase, a network-like La2Mg 17 phase, long period structure X phase-Mg 12 HREZn and Zr particle precipitation phase; the network-like La2Mg 17 phase is distributed along the α-Mg grain boundary, and the long-period structure X phase-Mg 12 HREZn precipitates and pins on La2Mg 17 phase; the Zr particles provide heterogeneous nucleation cores for α-Mg grains; the spherical α-Mg grain size is 3 to 15 μm, and the Zr particle size is 100 to 200 nm; the thermal conductivity of the die-cast magnesium alloy is 128 to 143 W·(m·K) -1 The ignition point is above 880℃, and the corrosion rate in 3.5wt% NaCl solution is 0.047~0.083mg / cm 2 / day, yield strength ≥160.2MPa.
2. A method for preparing a highly corrosion-resistant, flame-retardant and highly thermally conductive die-cast magnesium alloy as claimed in claim 1, characterized in that: The following steps are involved: 1) Put the regenerated magnesium ingot, zinc block and calcium block into the crucible of the resistance furnace, heat it to 690-720°C, sprinkle the commercial RJ-5 flux into the crucible, wait for the charge to be completely melted and evenly stirred, and then obtain a magnesium melt, heat the magnesium melt to 730-750°C, slowly add the rare earth metal La and HRE into the magnesium melt and stir for 10-15 minutes, sprinkle the RJ-5 flux into the magnesium melt and evenly stir, heat the magnesium melt to 750-780°C, add the Mg-Zr master alloy and pass argon into the melt for 5-10 minutes to accelerate alloying and melt homogenization; 2) introducing H2 / Ar mixed gas into the bottom of the crucible and sprinkling refining agent into the melt for refining, after refining, slag is removed and RJ-5 flux is sprinkled in for covering; the volume fraction of H2 in the H2 / Ar mixed gas is 5-8%; 3) The magnesium melt refined in step 2) is heated to 750-770° C., kept at this temperature for 10-20 minutes, and then the resistance furnace is powered off. The magnesium melt is naturally cooled to 700-730° C., and then sampled for testing. After the alloy composition is tested to be qualified, a magnesium alloy ingot is cast.
3. The method for preparing a highly corrosion-resistant, flame-retardant and highly thermally conductive die-cast magnesium alloy according to claim 2, characterized in that: In step 1), the flow rate of the argon gas introduced is 15-20 L / min, in step 2), the flow rate of the 5-8% H2 / Ar mixed gas introduced is 15-20 L / min, and the refining time is 15-25 min.
4. The method for preparing a highly corrosion-resistant, flame-retardant and highly thermally conductive die-cast magnesium alloy according to claim 2, characterized in that: The refining agent in step 2) is a mixture of commercial RJ-6 flux and MgF2, the amount of the refining agent added is 2% by weight of the magnesium melt, and the weight percentage of MgF2 in the refining agent is 10-30%; the total amount of RJ-5 flux used in step 1) and step 2) is 2% by weight of the magnesium melt.
5. The method for preparing a highly corrosion-resistant, flame-retardant and highly thermally conductive die-cast magnesium alloy according to claim 2, characterized in that: The casting of the magnesium alloy ingot in step 3) is carried out under the protection of a mixed gas of SF6 and CO2, wherein the volume ratio of SF6 is 0.1-0.3%.
Citation Information
Patent Citations
Composite rare earth Nd and Y added flame-retardant magnesium alloy and ignition point testing method thereof
CN103469040A
High-strength and high-corrosion-resistance ternary magnesium alloy and preparation method thereof
CN111304510A
High strength corrosion resistant rare earth cast magnesium alloy and preparation method thereof
CN101575683A
Cited By
Magnesium alloy and preparation method thereof
CN121802255A